84.7k views
2 votes
NO LINKS OR ANSWERING QUESTIONS YOU DON'T KNOW!!!!

Chapter 11 part 1:

How can a logarithmic functions be rewritten as its inverse (exponential function)?

User Blanka
by
4.3k points

1 Answer

7 votes

9514 1404 393

Answer:


\text{for }f(x)=\log_b(x),\text{ the inverse is }f^(-1)(x)=b^x

Explanation:

As with any function and its inverse, you can find the inverse of ...


f(x)=\log_b(x)

by solving the equation x = f(y).


x=\log_b(y)\\\\b^x=y\qquad\text{use as a power of b}\\\\\boxed{f^(-1)(x)=b^x}

User RomkaLTU
by
4.9k points